The Effectiveness of Combining Antibiotics and Antioxidants in the Treatment of Acute Bacterial Respiratory Tract Infections - Atjo, Neng Mira; Tanggono, Aninda (Jurnal Ar Ro'is Mandalika (Armada), 2025)
Acute bacterial respiratory tract infections (ABRTIs) remain a significant public health concern, particularly due to increasing antibiotic resistance and the resulting decline in treatment efficacy. In response, researchers have explored adjunctive therapies, including antioxidants, to enhance antibiotic performance and reduce oxidative stress-related complications. This study aims to evaluate the effectiveness of combining antibiotics with antioxidants in treating ABRTIs by employing a qualitative approach through systematic literature review and library research. Data were collected from peer-reviewed journals, scientific databases, and relevant academic publications spanning the last two decades. The findings reveal that oxidative stress plays a crucial role in the progression and severity of bacterial infections in the respiratory tract. Antioxidants such as N-acetylcysteine, vitamin C, and glutathione have shown promising synergistic effects when combined with conventional antibiotics. These combinations not only improve microbial clearance but also minimize tissue damage and inflammatory responses. Furthermore, the literature indicates a potential role for antioxidants in mitigating antibiotic-induced toxicity and in restoring immune balance. However, despite encouraging preclinical and limited clinical data, there remains a lack of large-scale, randomized controlled trials to confirm the therapeutic advantage of this combination. The study concludes that while the integration of antioxidants into antibiotic therapy appears promising, further empirical validation is essential. These findings highlight the importance of continued interdisciplinary research to optimize therapeutic protocols for ABRTIs.